In vitro effectiveness of the avocado peel extract (Persea americana Mill) as an antifungal against Trichophyton rubrum, the cause of dermatophytosis - Ariyati Yosi; Ira Armayanti; Meidina K. Wardani (Medicinski glasnik, 2023)
Aim: To determine the effectiveness of avocado peel extract (Persea americana Mill) as an antifungal against T. rubrum, which causes dermatophytosis. Methods: In vitro laboratory experimental study using a post-testonly control group design analysed active compounds of avocado peel and continued with the antifungal activity test. In each group divided according to the concentration of 0% (negative control), 12.5%, 25%, 37.5%, 50%, 62.5%, 75%, and positive control (2% ketoconazole) antifungal activity test was carried out using the fungus T. rubrum ATCC 28188 for five repetitions. Results: The avocado peel extract contained phenolic compounds, flavonoids, tannins, saponins, alkaloids, terpenoids, and glycosides. Antifungal activity test showed a significant difference with the highest mean inhibition zone diameter of T. rubrum, which was demonstrated at a concentration of 75%. Conclusion: Avocado peel extract is useful to inhibit growth of Trichophyton rubrum in dose dependent.
Keywords: avocado peel; dermatophytosis; Persea americana Mill.; Trichophyton rubrum